Surgical extremity preservation in severe acute limb ischemia in a 4-week-old newborn - Manuela Schulz; Johannes Hatzl; Katrin Meisenbacher; Christian Gille; Andreas S. Peters; Dittmar Böckler (Annals of Vascular Surgery - Brief Reports and Innovations)
This case report describes a successful revascularisation of severe acute limb ischemia (ALI) in a 4-week-old newborn following common femoral artery dissection due to catheterization for invasive blood pressure measurement during cardiac arrest in the intensive care unit. Iatrogenic acute limb ischemia in childhood is very rare and, in selected cases, a fatal condition potentially associated with limb loss and lifelong mobility impairments. The most common cause of acute limb ischemia in newborns is catheter-associated thrombosis. Current clinical guidelines recommend primary conservative management with heparin administration (level of recommendation: Class 1C) for children under 2 years of age. If revascularization is needed and indicated, open surgical techniques are typically performed. The following case report describes successful surgical treatment of acute limb ischemia in the context of current literature on ALI in childhood, including clinical presentation, diagnosis, treatment, and follow-up.